1997
DOI: 10.1073/pnas.94.4.1361
|View full text |Cite
|
Sign up to set email alerts
|

Highly purified CD25resting T cells cannot be infectedde novowith HIV-1

Abstract: Previous studies have demonstrated that the expression of CD25 can distinguish CD25 ؊ latently infected cells from CD25 ؉ cells actively producing virus. Our studies were designed to characterize the nature and stability of the viral genome in CD25 ؊ quiescent HIV-1-infected cells and to determine whether these cells could be infected Using a model of acute in vitro infection, we have previously demonstrated that the expression of CD25 can distinguish latently infected cells (CD25 Ϫ ) from cells actively produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 21 publications
1
50
0
1
Order By: Relevance
“…18,[26][27][28] We observed that, compared with TT-and C albicans-specific CD4 T cells, in which CD25 expression was evident, CMV-specific CD4 T cells expressed little CD25 18,25 (supplemental Figure 2A). This low CD25 expression on CMV-specific cells may be because CMV-specific CD4 T cells produced very little endogenous IL-2 in response to recall antigen stimulation 18 (data not shown).…”
Section: Phenotypic Characterization Of Cmv- Tt- and C Albicans-spementioning
confidence: 99%
“…18,[26][27][28] We observed that, compared with TT-and C albicans-specific CD4 T cells, in which CD25 expression was evident, CMV-specific CD4 T cells expressed little CD25 18,25 (supplemental Figure 2A). This low CD25 expression on CMV-specific cells may be because CMV-specific CD4 T cells produced very little endogenous IL-2 in response to recall antigen stimulation 18 (data not shown).…”
Section: Phenotypic Characterization Of Cmv- Tt- and C Albicans-spementioning
confidence: 99%
“…Further, it has been demonstrated that HIV and FIV replicate efficiently in CD4 ϩ CD25 ϩ T cells that are partially activated but not in naive CD4 ϩ CD25 Ϫ resting T cells (7,9,24,43). To date there have been limited reports regarding FIV replication in activated versus resting T cells.…”
mentioning
confidence: 99%
“…While HIV infection has also been demonstrated in naive T cells in vivo (33), establishment of a stable HIV infection in resting T cells in vitro remains controversial. Some studies suggest that HIV can efficiently bind and enter resting T cells (42,46), whereas others have shown that naive T cells are resistant to de novo HIV infection (9,19). In this regard, the data suggest that susceptibility of different lymphocyte subsets to HIV infection is regulated, to some extent, by differential expression of viral coreceptors.…”
mentioning
confidence: 99%
“…[1][2][3] Whether HIV productively infects naive T cells in vivo is still controversial. [4][5][6][7][8][9] Naive T cells were shown to harbor replicationcompetent HIV, 7,10 but are not an active site of HIV replication in the absence of mitogen stimulation. 11 Even in studies demonstrating HIV infection of naive T cells, further analysis of integrated HIV indicated that HIV DNA did not always integrate into the genome.…”
Section: Introductionmentioning
confidence: 99%